The Changing Da’wah Preference From Salafi to Moderate: Gus Baha and Habib Ja’far in Millennial Muslim Urban - Taufiq, Firmanda; Tsauro, Ahalla (Journal of Asian Wisdom and Islamic Behavior, 2025)
Da’wah preferences among urban Muslim millennials are likely changing recently due to the emergence of figures, namely Bahauddin Nur Salim (Gus Baha) and Habib Husein Ja’far Al-Hadar (Habib Ja’far). Da’wah materials offered by mainstream preachers in urban areas tend to be Salafi. Meanwhile, the two figures’ appearance gave a new color with a traditional Islamic pattern based on the nuances of pesantren. This study aims to examine the changes in da’wah preferences among millennial urban and the reason behind it. Through Stuart Hall’s circuit of culture theory, this study attempts to compare the two figures who became religious authority alternatives through da’wah methods in the stages of content production. This qualitative study is based on previous studies, preachers speeches through YouTube channels. The study shows that urban millennial generations have likely experienced changing preferences in da’wah which was originally consumptive listening to da’wah from several Salafi groups to the alternative moderate groups. Meanwhile, Habib Ja’far might be preferable among youngsters as he has a wider segmentation than Gus Baha.